1999
DOI: 10.1097/00000539-199907000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine Epidural Anesthesia and Analgesia Versus General Anesthesia and Intravenous Patient-Controlled Analgesia with Morphine in the Perioperative Management of Hip Replacement

Abstract: Compared with general anesthesia and postoperative IV patient-controlled analgesia with morphine, epidural anesthesia and analgesia with the new local anesthetic ropivacaine enables patients to be discharged sooner from a postanesthesia care unit and provides superior pain relief during the first 24 h after hip replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…If this occurs, the catheter should not be removed, but left in place to be used as an epidural catheter. 3 We do not believe that routine radiographic verification is necessary to confirm an assumed correct catheter position. We recommend radiographic assessment as a complement to careful clinical practice and surveillance only when an unusual catheter location is suspected.…”
Section: Radiographymentioning
confidence: 93%
See 1 more Smart Citation
“…If this occurs, the catheter should not be removed, but left in place to be used as an epidural catheter. 3 We do not believe that routine radiographic verification is necessary to confirm an assumed correct catheter position. We recommend radiographic assessment as a complement to careful clinical practice and surveillance only when an unusual catheter location is suspected.…”
Section: Radiographymentioning
confidence: 93%
“…1,2 Analgesia can also be achieved by either intravenous (IV) patient-controlled analgesia (PCA) or epidural analgesia, but these techniques may be associated with poor pain relief during movement and related side effects and technical problems. 3,4 In contrast to the "three-in-one" block, psoas compartment block techniques (PCB) are reliable in their ability to block the 3 main branches of the lumbar plexus (femoral, obturator, and lateral femoral cutaneous nerves). [5][6][7] The use of a catheter allows prolonged analgesia and facilitates an early rehabilitation.…”
mentioning
confidence: 99%
“…Three studies showed a tendency towards a higher incidence in general anaesthesia (evidence level II-III) [20,28,39]. Postoperatively, the reported effect of epidural analgesia on hypotension varied: frequency was either less (0% versus 33%, P=0.001, evidence level I), greater (40% versus 13%, P=0.01, evidence level II), or not different (evidence level II) as compared with patients receiving systemic analgesia [17,72,73]. Even though the evidence presented in the literature with regard to hypotensive events appears to be overwhelming, it must be remembered that the definition of hypotension is immensely diversified and ranges from a 20% decrease from baseline [28,32,49,65] to a systolic blood pressure of less than 90 mmHg [41].…”
Section: Hypotensionmentioning
confidence: 99%
“…administration of vagolytics (atropine, glycopyrrolate) or frequency-increasing sympathomimetics (ephedrine, dopamine, others) or negative sequelae. The postoperative incidence of bradycardia was assessed in two studies (evidence level II) [72,74] and one review [14] investigating total hip arthroplasty and did not significantly differ from either epidural nor regional anaesthesia.…”
Section: Arrhythmiamentioning
confidence: 99%
“…Among them, systemic opioids have been in use on a large scale in clinical practice [3,4]. However, systemic opioids can exhibit some deleterious sideeffects like sedation, nausea, vomiting, pruritus, urinary retention and bowel dysfunction.…”
Section: Introductionmentioning
confidence: 99%